Peningkatan Prestasi Belajar Mahasiswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Stad (Student Teams Achievement Divission) Pada Mata Kuliah Studi Kelayakan Bisnis - Sri Fitri Wahyuni (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
This study aims to determine and analyze the effect on improving student achievement on Business Feasibility Study course in Management Studies Program between before and after application of STAD type cooperative model. This research is an experimental research. The population in this study is all students of Semester V (five) Management Studies Program Faculty of Economics, University of Muhammadiyah North Sumatera that take Business Feasibility Study Course both the Morning and SIANG class in Odd Semester 2015/2016 academic year. While the sample is taken from the population with cluster random sampling technique, which is taking the number of students as much as 2 classes of all existing classes. Data collection techniques used are documentation. To analyze the data of this research is by using t-test formula. The result of the research shows that there is no significant difference of student achievement of class K Morning Management (control class) with the achievement of student study of Class A of Morning Management (class of experience) on Management Study Program of Economics Faculty of Muhammadiyah University of North Sumatera at 5% significant level with application of learning method Cooperative type STAD.